Phonetic Accommodation on the Segmental and the Suprasegmental Level of Speech in Native–Non-Native Collaborative Tasks - Ulbrich, Christiane (Language and speech, 2024)
This paper presents the investigation and analysis of speech accommodation effects in data obtained from Spanish learners of German with varying proficiency levels. The production data were recorded during a collaborative map task of the Spanish learners of German among each other and with a native speaker of German. The map task was designed to target words and phrases with specific segmental and suprasegmental characteristics. These characteristics were derived from contrastive analyses of Spanish and German. The main objectives of the paper were to investigate whether segmental and suprasegmental characteristics of the target language German are affected by phonetic accommodation to varying degrees and whether these differences depend on the proficiency level of the speaker or the interlocutor. The statistical analysis, using regression analyses, revealed inconsistent accommodation effects across learners of different proficiency levels as well as different linguistic phenomena. In line with previous findings the results can best be accounted for by an adaptation of a dynamic system approach.